The systemic analysis of the establishment of torture as foreign policy measure in modern democratic institutions with special reference to the use of torture during the “War on Terror” - Hough, Gys (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Political Science))--University 2010.